Impactos antrópicos, cambio climático, y vulnerabilidad de especies: el caso de Psidium guajava en la región sur del Ecuador - Ramirez Criollo, Leodan Vicente (2023)
The importance of working with the species Psidium guajava, is its level of adaptation and reproduction time, however, climate change is damaging directly and indirectly. This study evaluated the effects of climate change and changes in land use on the potential distribution of Psidium guajava L., under RCP 4.5 and 6.0 climate scenarios in the Southern Region of Ecuador implementing modeling techniques with Biomod 2, in which the modeling, calibration and evaluation of the models were executed jointly with R and QGis software, in addition to the bioclimatic and topographic variables implementing a variance inflation factor that measured the correlation of the variables and their strength in the distribution model of the species. The data of presence and pseudoscience’s were obtained from the herbarium of the National University of Loja, the results of potential distribution were submitted to the statistical test of ROC and TSS determined a value of 0.9 considered very good, covering an area of 1 401. 955 ha of potential distribution of the species, showing that the most suitable scenario was RCP 4.5 for the year 2050 with respect to the gain with 53% (~736 403 ha), greater loss in 2030 with 33% (463 862 ha) and persistence in 2080 with 73% (1 020 474 ha), while for the RCP 6 scenario. 0 gain and persistence were observed in the year 2080 with 52 % (~731 685 ha) and 76 % (~1 070 160 ha) respectively, and a loss of 41 % (~577 161 ha) for the year 2030, due to the temperature ranging from 19°C to 20°C, so that the species can be determined vulnerable, therefore, it was found that the most conclusive variables in this study were Bio1 (Mean annual temperature), Bio12 (Annual precipitation), and DEM (Digital Elevation Model).